2020
DOI: 10.18257/raccefyn.1062
|View full text |Cite
|
Sign up to set email alerts
|

La familia Elmidae (Insecta: Coleoptera: Byrrhoidea) en Colombia: riqueza taxonómica y distribución

Abstract: Los élmidos son una familia de escarabajos acuáticos muy frecuentes en ambientes lóticos y de amplia utilización como bioindicadores de la calidad de agua. Con el objetivo de reconocer la riqueza y la distribución de los géneros de Elmidae en Colombia, se revisaron e identificaron 22.150 ejemplares (larvas y adultos) recolectados y depositados entre 1976 y 2017 en varias colecciones entomológicas del país, en especial el Museo de Entomología de la Universidad del Valle. Los puntos de muestreo se ubicaron entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
2
4
0
1
Order By: Relevance
“…Further, some substantial differences in ecological requirements were predicted by the SDMs of elmid genera in the current research ( Figure 4 ). These differences are like previous studies [ 16 , 22 , 115 , 116 ], which found that genera in the Elmidae family differ regarding their ecological requirements. In this context, despite some relevant works that have been published on the taxonomy of the Ecuadorian Elmidae in the last few years [ 117 , 118 , 119 ], no work has been done about species distribution modelling of Elmidae.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Further, some substantial differences in ecological requirements were predicted by the SDMs of elmid genera in the current research ( Figure 4 ). These differences are like previous studies [ 16 , 22 , 115 , 116 ], which found that genera in the Elmidae family differ regarding their ecological requirements. In this context, despite some relevant works that have been published on the taxonomy of the Ecuadorian Elmidae in the last few years [ 117 , 118 , 119 ], no work has been done about species distribution modelling of Elmidae.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Austrolimnius and Heterelmis tolerate a wide temperature range and survive cold and relatively warm water. Given the tight inverse relationship between elevation and temperature [ 120 ], both findings of González-Córdoba et al [ 22 ] fit with the current research, where the higher probability of spatial occurrence of Austrelmis is between 3111 and 3833 m a.s.l. ( Figure 4 and Figure 5 ), whilst Austrolimnius and Heterelmis tend to occur at higher and lower elevation streams (ranges between 3043 and 3833 and 2734 and 3798 m a.s.l., respectively).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…El orden Ephemeroptera también fue uno de los más abundantes y con mayor distribución; Camelobaetidius se asoció con velocidades medias y menores altitudes; Baetodes con mayores velocidades y altitudes, al igual que Anacroneuria (Plecoptera), Atopsyche y Smicridea (Trichoptera), que presentan adaptaciones para esos tipos de hábitats (Bispo, et al, 2006;Schmitt, et al, 2016). Entre los Coleoptera están los asociados a corrientes con velocidades medias: Psephenus (Psephenidae) y Heterelmis (Elmidae), aunque este último es característico de ambientes con altas velocidades y elevado contenido de oxígeno (Manzo, 2013;González-Córdoba, et al, 2020), así como larvas de Simulium (Diptera) (Coscarón-Arias, 2009), que pueden sobrevivir en condiciones temporales de anoxia alimentándose de materia orgánica, por lo que están presentes en diferentes ambientes (Docile, et al, 2015), tal como se recoge en el análisis de ACC.…”
Section: Discussionunclassified